2018
DOI: 10.3389/fpsyg.2018.01482
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Academic and Psychological Impact of the Transition to Secondary Education

Abstract: The transition from primary to secondary education is one of the most stressful events in a young person’s life (Zeedyk et al., 2003) and can have a negative impact on psychological well-being and academic achievement. One explanation for these negative impacts is that the transition coincides with early adolescence, a period during which certain psychological disorders (i.e., anxiety disorders) become more salient (Kessler et al., 2005) and marked social, biological, and psychological development occurs (Ande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
138
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 152 publications
(224 reference statements)
6
138
1
7
Order By: Relevance
“…Some set a clear lower and upper year range (Benner, ; Hanewald, ), others set an upper but not a lower year limit (Symonds & Galton, ; Pearson et al , ), others did not specify the time period (Topping, ; Cantali, ; Evans, Borriello, & Field, ) and two papers did not stipulate the time period as one of the inclusion criteria but reported on the time range covered by included papers (Hughes et al , ; van Rens, Haelermans, Groot, & van den Brink, ). Seven reviews explicitly reported inclusion and/or exclusion criteria in the search methodology and in two papers (Cantali, ; Evans et al , ) the criteria are inferred from the focus of the review. The range and diversity of the inclusion and exclusion criteria limit our ability to draw conclusions based on a meta‐synthesis of the reviews.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some set a clear lower and upper year range (Benner, ; Hanewald, ), others set an upper but not a lower year limit (Symonds & Galton, ; Pearson et al , ), others did not specify the time period (Topping, ; Cantali, ; Evans, Borriello, & Field, ) and two papers did not stipulate the time period as one of the inclusion criteria but reported on the time range covered by included papers (Hughes et al , ; van Rens, Haelermans, Groot, & van den Brink, ). Seven reviews explicitly reported inclusion and/or exclusion criteria in the search methodology and in two papers (Cantali, ; Evans et al , ) the criteria are inferred from the focus of the review. The range and diversity of the inclusion and exclusion criteria limit our ability to draw conclusions based on a meta‐synthesis of the reviews.…”
Section: Introductionmentioning
confidence: 99%
“…children with disabilities) (Hanewald, ; Symonds & Galton, ; van Rens et al , ), and one review excluded papers in a particular curriculum area (Hanewald, ). One paper focused exclusively on children with profound and multiple learning disabilities (PMLD) (Cantali, ), one review compared children with SEN and their peers (Hughes et al , ), three papers focused on typically developing children (Hanewald, ; Symonds & Galton, ; van Rens et al , ), and four reviews did not specify whether papers involving children with additional support needs (ASN) were included or excluded (Benner, ; Topping, ; Pearson et al , ; Evans et al , ), although it could be inferred from cited studies (e.g. Evans et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…This is needed for two reasons. First, the findings of studies on school transitions have shown that males and females are differently affected by such transitions (Simmons & Blyth, 2008;Evans, Borriello, & Field, 2018). According to Blyth, Simmons and Carlton-Ford (1983, p. 106), female students' sensitivity to school changes could be attributed to the greater perceived importance of social relationships for females in the society.…”
Section: Research Questionsmentioning
confidence: 99%
“…Biologically, adolescence marks an age when the fundamental properties of the circadian timekeeping system change and develop [5]. Socially, the daily routines of students change as they transition from high school to higher secondary schools [6,7]. Psychologically, study pressures and reduced school connectedness lower their mental health [8].…”
Section: Introductionmentioning
confidence: 99%